ANALISIS PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) DALAM PEMBANGUNAN BERKELANJUTAN DI JAWA TIMUR DENGAN PRESPEKTIF POLICY GOVERNANCE - Mustofa, Amirul (Jurnal Demokrasi, 2012)
The involvement of community empower companies to participate in sustainable development through Corporate Social Responsibility (CSR) programs in the era of governance are important, particularly those intended for rural or marginalized communities. However, in East Java, policies on the CSR program have not been well established, so the cooperation between the corporate governance management with the government's CSR program has not demonstrated synergic performance. Such conditions have not been determined due to the lack of operational level policy (government regulation) so that the CSR program in East Java Provincial Government has not performed well. The purpose of this paper is to analyze what and how governance reforms that needed to be done so that the CSR program performs well. Keywords: Corporate Social Responsibility, Governance Reform, and Corporate Governance.